INSIDERS AND CORPORATE INCOME STREAMS. - Nerlove, S. H. (The Accounting Review, 1930)
Abstract No one knows precisely what portion of the income-streams of corporations goes to the "insiders." Insiders are the executive head of a business firm. He is typically on the board of directors and is acquainted first-hand with practically all the policies, the future plans and past operations of the business unit in question. Practically always bankers and very often the members of professional firms, such as, management, legal, accounting or engineering concerns might be considered "insiders." The indicated income-stream of a given business firm over short periods of time can be changed radically by the "insiders." And these changes can be so made that over a long period of time the income-streams to the "insiders" will be enhanced over what they would otherwise be. They can manipulate the accounting practices of the business unit, thereby affecting the amount that will be considered as the profit-share during any given period of time. The manipulation of accounts-takes the form usually of tampering with the valuation of assets and liabilities.